Storm-triggered Landslides in Warmer Climates - Ren, Diandong. (Springer International Publishing : Imprint: Springer, 2015)
This volume covers the general physics of debris flows and various approaches to modeling - including the SEGMENT-Landslide approach – as well as the pros and cons of these approaches, and how other approaches are sub-sets of the SEGMENT-Landslide approach. In addition, this volume will systematically unify the concepts of vadose zone hydrology and geotechnical engineering, with special emphasis on quantifying ecosystem consequences of storm-triggered landslides in a warmer climate setting. The reader will find a comprehensive coverage of concepts ranging from hillslope hydrology, porous granular material rheology, and the fundamentals of soil properties to state-of-the-art concepts of enhanced hydrological cycle with climate warming, finishing with a discussion of new approaches for future research.